The strength of direct selection against female promiscuity is associated with rates of extrapair fertilizations in socially monogamous songbirds - Albrecht, Tomás; Kreisinger, Jakub; Piálek, Jaroslav (The American naturalist, 2006)
A costs-benefits approach has frequently been used to understand the evolutionary origin and maintenance of promiscuity in animal populations. Recent meta-analyses suggest that direct costs to unfaithful females outweigh indirect benefits from infidelity in socially monogamous songbirds, suggesting that in this taxa, extrapair fertilization (EPF) evolved primarily as a self-interest male tactic. Here we present results of comparative analysis to show that standardized selection gradients acting against female infidelity (direct costs of promiscuity) explain variation in EPF rates at an interspecific level in passerines. This result confirms that costs to females resulting from reduced parental care from cheated males constrain promiscuity in this group. Our data indicate that females exert resistance over EPFs when the costs of infidelity are high and, conversely, that the rate of EPFs increases when selection on females to defend themselves against EPF attempts by males is weak and costs of infidelity are low.
Keywords: Reproduction; rozmnožování; druhová specificita; Nesting Behavior; Phylogeny; Sexual Behavior, Animal; Biological Evolution; Female; Songbirds; zvířata; ženské pohlaví; fylogeneze; biologická evoluce; hnízdění; Species Specificity; zpěvní ptáci; Animals; sexuální chování zvířat; selekce (genetika); Selection, Genetic